Suckling behaviour and allonursing in the Apennine chamois. Issue 5 (3rd September 2018) - Scornavacca, Davide; Cotza, Antonella; Lovari, Sandro; Ferretti, Francesco
Abstract : Maternal cares and, in particular, suckling behaviour, are fundamental for early growth and survival of offspring ungulates. In turn, factors influencing maternal cares can have important effects at individual and population levels, with consequences at both short and long temporal scales. We assessed monthly variation of behavioural indices of suckling and nursing, as well as occurrence of allosuckling, in a mountain-dwelling ungulate, the Apennine chamois Rupicapra pyrenaica ornata, on summer-early autumn 2013–2014. Not surprisingly, duration of suckling events and frequency of suckling solicitations by kids, decreased throughout months, whereas the proportion of grazing kids increased from July to October, indicating a growing reliance on pasture. Conversely, the probability of suckling success kept stable from July to October, suggesting a constant willingness of females to allow kids to suckle. Of all suckling events, 63% involved more than one kid, indicating allosuckling. On average, multiple suckles were shorter than those involving one kid and occurred in all months with the same proportion. Our results suggest the occurrence of high levels of maternal cares in a gregarious herbivore, with frequent allosuckling and apparent willingness of females to nurse offspring throughout summer-autumn. These results suggest that the mother's role does not terminate with weaning.